Global value chains, trade shocks and jobs: An application to Brexit. (24th March 2022) - Vandenbussche, Hylke; Connell, William; Simons, Wouter
Abstract: We develop a network trade model with country‐sector level input–output linkages with the objective of evaluating the impact of trade shocks. This framework is particularly useful to decompose the direct and the indirect trade effects of both a bilateral and a third country trade shock, evaluated at the country‐sector level. Using the sectoral World Input–Output Database (WIOD) combined with sectoral employment data, we evaluate the impact in terms of value added and employment of different scenarios of Brexit for 56 industries in the 27 Member States of the European Union, as well as the United Kingdom. In this respect, we consider both the results under the current EU–UK Trade agreement, as well as a counterfactual scenario in which WTO tariffs would apply. In contrast to other studies, we find EU‐27 value added and job losses to be substantially higher than hitherto believed as a result of the closely integrated EU network structure. Our approach finds that upstream sectors are particularly vulnerable to indirect trade shocks effects due to their network centrality.